2020
DOI: 10.3390/app10155054
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesized ZnO Nanoparticles Mediated by Mentha Spicata Extract Induce Plant Systemic Resistance against Tobacco Mosaic Virus

Abstract: Globally, plant viral infection is one of the most difficult challenges of food security, where considerable losses in crop production occur. Nanoparticles are an effective control agent against numerous plant pathogens. However, there is limited knowledge concerning their effects against viral infection. In the present study, the green synthesis of zinc oxide nanoparticles (ZnO NPs) using aqueous leaf extract of Mentha spicata was achieved. X-ray diffraction patterns confirmed the crystalline nature of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(51 citation statements)
references
References 72 publications
(60 reference statements)
3
40
0
Order By: Relevance
“…The leaf extract was combined with 1-mM ZnNO 3 (Sigma-Aldrich, India) solution and was stirred at room temperature (35 ± 2 °C) for 1 h. A brown-yellowish precipitate was heated under stirring at 60 °C for 4 h and further, the solution was continuously stirred at room temperature for 24 h 18 . The precipitate was dried at 100 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaf extract was combined with 1-mM ZnNO 3 (Sigma-Aldrich, India) solution and was stirred at room temperature (35 ± 2 °C) for 1 h. A brown-yellowish precipitate was heated under stirring at 60 °C for 4 h and further, the solution was continuously stirred at room temperature for 24 h 18 . The precipitate was dried at 100 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Fourier transform infrared spectroscopy (FT-IR) analysis was carried out using a spectrum 65 FT-IR spectrometer (PerkinElmer Co., Ltd., Massachusetts, USA). ZnO NPs were used for scanning electron microscopy (FEI QUANTA-200; SEM), energy-dispersive X-ray spectroscopy (EDX) 18 . XRD pattern were recorded using Cu Kα radiation at a wavelength of 1.54060 Å, with a nickel monochromator in the 2θ range from 10° to 80° using an analytical X-PERT PRO, diffractometer.…”
Section: Methodsmentioning
confidence: 99%
“…After treatment with RNase-free DNase to eliminate genomic DNA, the concentration and quality of the extracted RNA were determined at A 260/ A 280 and A 260/ A 230 using SPECTROstar Nano (BMG Labtech, Ortenberg, Germany). In contrast, the integrity of the RNA was assessed by the agarose gel electrophoresis technique [ 56 ]. First-strand cDNA was synthesized using 1 μg of total RNA with random oligohexamers and oligo (dT) primers, as described previously [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…The green synthesis of NPs using plant extracts offers an alternative and promising approach in the production of safer and environmentally friendly nanoparticles [ 28 , 29 ]. According to [ 30 ], the eco-friendly biosynthesized NPs provides an alternative to the chemically synthesized ones, which should lower the chemical toxicity in the natural environments.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that the chemical synthesized silver NPs is 10 times more toxic than the green synthesized nanoparticles for Artemia nauplii [ 32 ]. Another recent review recommends the potential use of the green synthesized ZnO-NPs as growth promotors, also, to increase resistance against viral infection [ 28 ]. Furthermore, ZnO-NPs have been found to exert cytotoxic activity against cancer cells in addition to their promising antimicrobial activity [ 33 ].…”
Section: Introductionmentioning
confidence: 99%